Microbial diversity and bacterial biocatalytic activities in pitcher fluid of Nepenthes sp. / Chan Xin Yue - Chan , Xin Yu (2019)
Carnivorous pitcher plant, Nepenthes, develops pitcher-shaped pitfall trap, which is equipped with enzymatic fluid for prey digestion, as an alternative nutrient acquisition strategy. Despite of the antimicrobial compounds and pitcher fluid acidification by Nepenthes plant, the pitcher fluids host a range of micro- and macro-organisms. In this study, metagenome samples were extracted from the pitcher fluids of wild Nepenthes albomarginata, Nepenthes gracilis and Nepenthes sanguinea, and Nepenthes hookeriana planted in nursery. Metagenomic samples and bacterial 16S rRNA amplicons were subjected to next generation sequencing. Analysis on the bacterial 16S rRNA sequences showed that Proteobacteria, Bacteroidetes, Actinobacteria, Acidobacteria and Firmicutes were the dominant bacteria phyla in pitcher fluid. Highly acidic pitcher fluids were dominated by alphaproteobacterial genus Acidocella and Acidisoma. Meanwhile, more diverse bacterial communities were observed in low acidity pitcher fluids. The bacterial community assemblage was strongly influenced by the pitcher fluid acidity. Besides, eukaryotic community namely insects, arachnids, fungi and protista were found in the pitcher fluids based on eukaryotic 18S rRNA genes extracted from metagenomic data. The viral community was predominated by Dasheen mosaic virus, followed by Vicia cryptic virus or Bombyx mori nucleopolyhedrovirus. To my knowledge, this is the first report on the microbial community composition in the pitcher fluid of N. sanguinea. From the metagenomic data, the detection of genes coding for the key enzymes in chitin, N-acetylglucosamine and protein hydrolysis suggested the contribution of inhabitant in Nepenthes pitcher fluid in the catabolism of insect exoskeleton, which is mainly composed of chitin and protein extracellular matrix. On the other hand, allantoin was suggested as an alternative nitrogen source for the pitcher fluid’s microbial community pitcher fluid when preferred nitrogen is depleted. The ammonia generated during insect and allantoin degradation might be assimilated by glutamine synthetase for glutamine synthesis. Furthermore, fermentation of xylose by bacteria in pitcher fluid was also suggested as the key enzymes in xylose isomerase pathway were found in the metagenome data. The bacterial biocatalytic activities were tested using 18 bacteria isolates from pitcher fluid. Among the isolates, positive results in chitinolytic (β-N-acetylglucosaminidase, chitobiosidase and endochitinase), proteolytic, xylanolytic, cellulolytic or amylolytic activity tests were observed from 11 strains. In addition, 13 putative GH18 chitinase genes and 2 putative GH19 chitinase genes were determined from the genome of Klebsiella, Pseudomonas, Serratia and Bacillus strains isolated from the pitcher fluids. Insect degradation ability of the isolated strains was tested on sterilized Drosophila melanogaster. Although insect disintegration was not observed in this test, the contribution of bacteria in insect degradation cannot be ruled out as colonization of bacteria on D. melanogaster were observed. D. melanogaster with bloated abdomen was found in the medium inoculated with bacteria indicated the bacteria putrefaction activity. Besides, colonization of bacteria on insect was more successful in experiment using multiple bacteria strains. The synergistic interactions between pitcher fluid inhabitants and Nepenthes plant were believed to enhance their survival in nutrient limiting environment.